2020
DOI: 10.1042/bsr20200527
|View full text |Cite
|
Sign up to set email alerts
|

MiR-22-3p suppresses sepsis-induced acute kidney injury by targeting PTEN

Abstract: Background: Septic acute kidney injury is considered as a severe and frequent complication that occurs during sepsis. The present study was performed to understand the role of miR-22-3p and its underlying mechanism in sepsis-induced acute kidney injury. Methods: Rats were injected with adenovirus carrying miR-22-3p or miR-NC in the caudal vein before cecal ligation. Meanwhile, HK-2 cells were transfected with the above adenovirus following LPS stimulation. We measured the markers of renal injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 49 publications
(56 reference statements)
2
29
0
Order By: Relevance
“…Moreover, we found the upregulation of miR-22-3p alleviated airway inflammation in the OVA-induced murine asthma model. In line with our observation, miR-22-3p notably curbed the inflammation and apoptosis by lowering the levels of IL-1β and IL-6 in rats with sepsis-induced acute kidney injury and in HK-2 cells exposed to LPS (Wang et al, 2020b). Therefore, these findings showed that miR-22-3p may participate in the pathogenesis of asthma.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we found the upregulation of miR-22-3p alleviated airway inflammation in the OVA-induced murine asthma model. In line with our observation, miR-22-3p notably curbed the inflammation and apoptosis by lowering the levels of IL-1β and IL-6 in rats with sepsis-induced acute kidney injury and in HK-2 cells exposed to LPS (Wang et al, 2020b). Therefore, these findings showed that miR-22-3p may participate in the pathogenesis of asthma.…”
Section: Discussionsupporting
confidence: 90%
“…With the rapid development of high-throughput sequencing, a number of miRNAs were identified to be involved in PTEN downregulation. miR-22 has been proved to downregulate PTEN in many different cell types via directly binding to the 3’UTR of PTEN 39 , 40 . In this study, we found MIR22HG overexpression significantly promoted miR-22 expression in hBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt pathway is regulated by several miRNAs, such as miR-202-5p [28], miR-101 [29,30], and miR-22-3p [31], which are upregulated in LFF-EVs. It was reported that exosomes promote GCs' proliferation through the P13K-AKT signaling [12] and MAPK signaling pathways [24].…”
Section: Discussionmentioning
confidence: 99%